Information materials in public libraries in Singapore : a study of material availability in library @ Orchard. - Ong, Hui Pheng. (2008)
This availability study adopted Kantor's classic availability analysis model. Such availability studies had been conducted at various libraries in the past decades to determine the effectiveness of libraries and the extent to which users succeeded in finding the materials that they need during their visits to the libraries.